IMPLEMENTASI MODEL PBL BERBANTUAN E-LKPD QUIZIZZ KONSEP EKOSISTEM TERHADAP HASIL BELAJAR PESERTA DIDIK KELAS X SMA - Wulandari, Ayu; Putra, Aminuddin Prahatama (UNIVERSITAS MUHAMMADIYAH METRO, 2025)
Low academic achievement among students remains a challenge in biology education, particularly in understanding environmental concepts. This issue is exacerbated by the dominance of lecture-based instruction and the limited use of interactive digital media. This study aims to evaluate the effect of applying the Problem-Based Learning (PBL) model integrated with the e-LKPD Quizizz platform on students’ learning outcomes in the topic of ecosystems. A quantitative approach was employed using a quasi-experimental design with a non-equivalent control group. The research involved two 10th-grade classes at SMA Negeri 3 Banjarmasin, selected through purposive sampling: class X-E as the experimental group and class X-B as the control group. The instruments used included affective observation sheets, psychomotor assessments, and cognitive learning achievement tests (pretest and posttest). Data were analyzed using SPSS version 30, involving N-Gain calculations, t-tests, homogeneity, and normality tests. The results showed that the experimental class achieved higher posttest scores than the control class, with N-Gain values in the moderate to high range. Improvements were also observed in affective and psychomotor learning outcomes. These findings demonstrate that the integration of the PBL approach with the e-LKPD Quizizz platform fosters active learning, enhances conceptual understanding, and improves cognitive, affective, and psychomotor outcomes in ecosystem learning.